HUBUNGAN POLA ASUH ORANG TUA TERHADAP KEMANDIRIAN ANAK KELAS B DI TKN 1 PLUS BANYUASIN III - Simamora, Ersi Sella; Rukiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between parenting styles and the independence of Class B children at TKN 1 Plus Banyuasin III. The study employed a quantitative method with an ex post facto design and total sampling technique involving 73 respondents. Data were collected through a closed questionnaire using a four-point Likert scale. Validity test results showed that all items were valid (r count > 0.227) and reliable (Cronbach's Alpha > 0.60). The normality test yielded Asymp. Sig. 0.200 > 0.05 and the linearity test yielded Sig. 0.517 > 0.05. The regression equation obtained was Ŷ = 83.546 − 0.229X with t count = −2.105 and Sig. 0.039 < 0.05, so Hₐ is accepted — parenting style has a significant effect on children's independence. The R² value of 0.059 indicates that parenting style contributes 5.9%, while 94.1% is influenced by other factors outside the model.